Attentional bias in competitive situations: winner does not take all - Sun, Zhongqiang; Bai, Tian; Yu, Wenjun; Zhou, Jifan; Zhang, Meng; Shen, Mowei (Frontiers in Psychology, 2015)
Compared to previous studies of competition with participants’ direct involvement, the current study for the first time investigated the influence of competitive outcomes on attentional bias from a perspective of an onlooker. Two simple games were employed: the Rock-Paper-Scissors game (Experiment 1) in which the outcome is based on luck, and Arm-wrestling (Experiment 2), in which the outcome is based on the competitors’ strength. After observing one of these games, participants were asked to judge a stimulus presented on either the winner’s or loser’s side of a screen. Both experiments yielded the same results, indicating that the onlookers made much quicker judgments on stimuli presented on the loser’s side than the winner’s side. This suggests the existence of an attention bias for loser-related information once a competition has ended. Our findings provide a new lens through which the influence of competition results on human cognitive processing can be understood.